Crimean–Congo Hemorrhagic Fever Virus Survey in Humans, Ticks, and Livestock in Agnam (Northeastern Senegal) from February 2021 to March 2022 - Moufid Mhamadi; Aminata Badji; Idrissa Dieng; Alioune Gaye; El Hadji Ndiaye; Mignane Ndiaye; Moundhir Mhamadi; Cheikh Talibouya Touré; Mouhamed Rassoul Mbaye; Mamadou Aliou Barry; Oumar Ndiaye; Babacar Faye; et al. (Tropical Medicine and Infectious Disease, 2022)
Crimean–Congo hemorrhagic fever virus (CCHFV) is widespread in Asia, Europe, and Africa. In Senegal, sporadic cases of CCHFV have been reported since 1960. Bordering Mauritania in northeastern Senegal, Agnam is an arid area in the region of Matam where CCHFV is endemic, which harbors a pastoralist community. Given the drought conditions of Agnam, inhabitants are in constant movement with their animals in search of pasture, which brings them into contact with pathogens such as arboviruses. To identify CCHFV in this area, we established a One Health site in order to analyze animal livestock, ticks and human samples collected over a one-year period by qRT-PCR and ELISA. Our analysis showed one (1/364) patient carried anti-CCHFV IgM and thirty-seven carried anti-CCHFV IgG (37/364). In livestock, anti-CCHFV IgG was detected in 13 (38.24%) of 34 sentinel sheep. The risk of CCHFV infection increased significatively with age in humans (p-value = 0.00117) and sheep (p-value = 1.18 × 10−11). Additional risk factors for CCHFV infection in sheep were dry seasons (p-value = 0.004) and time of exposure (p-value = 0.007). Furthermore, we detected a total of three samples with CCHFV RNA within Rhipicephalus evertsi evertsi and Rhipicephalus guilhoni tick species. Our results highlighted the usefulness of a One Health survey of CCHFV in pastoral communities at risk of arboviruses.